COCONUT AGRICULTURAL RESEARCH IN THE PHILIPPINES ITS HISTORY, TECHNOLOGICAL ADVANCES AND FUTURE TARGETS - Dr. SEVERINO S. MAGAT (International Coconut Community, 1992)
The paper deals with selected aspects of agricultural research on coconuts in the Philippines as follows : (a) a historical review; (2) agricultural research system; (3) scientific and technological advances and findings; and (4) future development oriented targets. Recognizing the need to support the development of the coconut industry under a sustainable and profitable coconut farming environment, the R & D Thrusts of agricultural research centers on : 1) Varietal Improvement; 2) Cultural and Fertilizer Management (with emphasis on Integrated Soil Fertility Management; 3) Integrated Crop Protection; 4) Cadang‑cadang disease control; 5), Processing and Utilization of Coconut Wood; and 6) Technical Support Services and Advisory Development.